The relationship between the female athlete triad and injury rates in collegiate female athletes - Edama, Mutsuaki (PeerJ, 2021)
BACKGROUND: This study aimed to clarify the relationship between the triad risk assessment score and the sports injury rate in 116 female college athletes (average age, 19.8 ± 1.3 years) in seven sports at the national level of competition; 67 were teenagers, and 49 were in their 20s. METHODS: Those with menstrual deficiency for >3 months or <6 menses in 12 months were classified as amenorrheic athletes. Low energy availability was defined as adolescent athletes having a body weight <85% of ideal body weight, and for adult athletes in their 20s, a body mass index ≤17.5 kg/m(2). Bone mineral density (BMD) was measured on the heel of the right leg using an ultrasonic bone densitometer. Low BMD was defined as a BMD Z-score <−1.0. The total score for each athlete was calculated. The cumulative risk assessment was defined as follows: low risk (a total score of 0–1), moderate risk (2–5), and high risk (6). The injury survey recorded injuries referring to the injury survey items used by the International Olympic Committee. RESULTS: In swimming, significantly more athletes were in the low-risk category than in the moderate and high-risk categories (p = 0.004). In long-distance athletics, significantly more athletes were in the moderate-risk category than in the low and high-risk categories (p = 0.004). In the moderate and high-risk categories, significantly more athletes were in the injury group, whereas significantly more athletes in the low-risk category were in the non-injury group (p = 0.01). Significantly more athletes at moderate and high-risk categories had bone stress fractures and bursitis than athletes at low risk (p = 0.023). DISCUSSION: These results suggest that athletes with relative energy deficiency may have an increased injury risk.